Kajian Kemampuan Rosela (Hisbiscus Sabdariffa) Dalam Menghambat Peningkatan Tekanan Darah Melalui Respon Vasodilator Nitrit Oksida pada Wanita Lanjut Usia penderita Hipertensi - I Yusni; M Syahrul (Jurnal Kardiologi Indonesia, 2012)
Background. Herbal medication for hypertension is common in population. This study aims to seek the role of nitric oxide (NO) in the mechanism of blood pressure reduction after  administration of rosella tea (hisbiscus sabdariffa). Methods. A pre-post study was conducted in elderly hypertensive women at UPTD Rumoh Sejahtera Banda Aceh. Subjects were given 2 grams rosella tea after meal twice a day for 3 weeks.  Sistolic and diastolic blood pressure, and NO concentration were compare pre and post rosella administration between control and experiment groups.Results. Rosela group has lower systolic and diastolic pressure as compare to control group (140,00 ± 10,00 vs 142,85 ± 4.87 mmHg; 84,28 ± 5,34 vs 89,28 ± 4,87mmHg, p < 0.05  respectively). Systolic pressure reduction by rosella was 14,77% with average pressure reduction of 24,28 mmHg. Diastolic pressure reduction was 9,22% with averagepressure reduction of 8,57 mmHg. No significant difference of nitric oxide concentration between groups (4,85 ± 2,16 vs 4,55 ± 3,11 µM, p>0.05). Conclusion. Rosella reduce systolic and diastolic blood pressure of elderly hypertensive women with mechanism out of nitric oxide level.